Evaluation of Turkish Juvenile Criminal Law in the Context of the Convention on the Rights of the Child - Ünver, Yener (Children’s Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges: Exploring Opportunities and Challenges, 2025)
Türkiye has ratified many international conventions regarding child rights and has regulated most, if not all, situations on the subject by law. However, it is obvious that there are many incomplete legal regulations and that the State does not fulfill many of its duties in daily life. Children cannot be adequately protected due to the statistical studies conducted in this field, the scandalous cases reported almost every week, and the negligence of official institutions in their duties. Many children are killed, severe acts of violence are committed against children by parents and teachers, both at home and in schools, children are subjected to sexual abuse at home and at school, in dormitories or nurseries, and the ages of the victim children are often very low. In addition, significant violations include the use of narcotics at very young ages, the abduction of children from their parents or siblings to prevent contact, the neglect of compulsory medical examinations and vaccinations, the failure to find missing children, and the failure to protect children involved in crimes, whether perpetrators or victims. In Türkiye, these violations against children preoccupy national courts and also supranational courts, and the number of cases is increasing day by day.